Histological Alteration of Green Mussel Perna viridis Organs Exposed to Microplastics - Nur Fadhilah Rahim; Khusnul Yaqin (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2022)
Microplastic in the oceans might interfere the health of marine organisms, including the green mussels (Perna viridis). This is due to microplastic accumulation in mussels organs, such as gills, hepatopancreas, and gonads. Therefore, tissue alteration is a good indicator for ecological risk analysis and other ecotoxicological study activities. Green mussels with shells 4.1 to 5.0 cm in length were collected from Mandalle waters, Pangkep Regency (Pangkajene Islands), Indonesia. Green mussels were exposed for seven days to microplastic with concentrations of  0.05 (A), 0.5 (B), and 5 (C) g/L. The results showed that the higher the concentration of microplastics exposed to the green mussel, the higher the accumulation of microplastics in the body of the mussel, within the tested concentrations. The increased concentration of microplastics increased the level of tissue alteration in the gills, hepatopancreas, and gonads, with the most sensitive organ being the hepatopancreas. Overall, the study confirmed that the histological assay of mussel organs could be used as a biomarker in ecotoxicological studies.